2021
DOI: 10.2478/fon-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nurse's happiness: a systematic review

Abstract: Objective An acute shortage of nurses exists all over the world. Part of this shortage appears to be due to nurses’ low job satisfaction, low retention, and high turnover. Happiness at work is identified as a contributing factor that determines the shortage of nurses across the world. This paper critically appraised the existing scientific articles that assessed the individual and organizational predictors of happiness among nurses. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
0
6
0
2
Order By: Relevance
“…It has been reported that the happiness of nurses is affected by various factors such as gender, age, professional working years, marital status, physical health status, quality of life, reason for choosing nursing, salary satisfaction, workload, patient profile, interpersonal relationships, cognitive flexibility, and emotion management skills [ 15 , 16 , 18 , 19 , 32 , 33 ]. In this study, it was concluded that happiness in nurses was not affected by age, gender, years of employment, educational level, or monthly income level, but it was related to marital status, doing additional income-generating work, desire to work as a nurse abroad, satisfaction with income, the ability of income to meet needs, the value that is the most important source of happiness (health, love, and money), and the level of personal development in the last five years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the happiness of nurses is affected by various factors such as gender, age, professional working years, marital status, physical health status, quality of life, reason for choosing nursing, salary satisfaction, workload, patient profile, interpersonal relationships, cognitive flexibility, and emotion management skills [ 15 , 16 , 18 , 19 , 32 , 33 ]. In this study, it was concluded that happiness in nurses was not affected by age, gender, years of employment, educational level, or monthly income level, but it was related to marital status, doing additional income-generating work, desire to work as a nurse abroad, satisfaction with income, the ability of income to meet needs, the value that is the most important source of happiness (health, love, and money), and the level of personal development in the last five years.…”
Section: Discussionmentioning
confidence: 99%
“…Happiness not only brings a sense of well-being to individuals but also leads to optimism and hopeful attitudes toward the future, enabling innovative and productive choices [ 15 ]. When nurses perceive fair treatment, they tend to have more trust in their work and their supervisors, thus working with hope and motivation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing organisational happiness is crucial to lowering academic personnel turnover (Awang et al, 2015). Employee turnover is primarily influenced by the happiness of employees (Qubaisi, 2017;Arulappan et al, 2021). Employee turnover is a well-known organisational consequence that occurs at a great expense to organisations as it ultimately reduces productivity.…”
Section: Employee Happiness and Turnover Intentionsmentioning
confidence: 99%
“…Happy people experience the feeling of security, make decisions more easily, and have a more participatory spirit [ 9 ]. Personal, psychological, family, social, and spiritual components are the individual predictors of happiness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%